2014
DOI: 10.1016/j.taap.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 7,12-dimethylbenz[a]anthracene exposure on connexin gap junction proteins in cultured rat ovaries

Abstract: 7,12-dimethylbenz[a]anthracene (DMBA) destroys ovarian follicles in a concentration-dependent manner. The impact of DMBA on connexin (CX) proteins that mediate communication between follicular cell types along with pro-apoptotic factors p53 and Bax were investigated. Postnatal day (PND) 4 Fisher 344 rat ovaries were cultured for 4 days in vehicle medium (1% DMSO) followed by a single exposure to vehicle control (1% DMSO) or DMBA (12.5 nM or 75 nM) and cultured for 4 or 8 days. RT-PCR was performed to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…An experiment [13] on rats shows that prenatal expoused to BaP leads offsprings premature ovarian failure and ovarian tumorigenesis. A Study concerning the effect of PAH on follicular growth [14] showed that mice exposed to cigarette smoke could reduce antral follicles, therefore leading to appropriate preovulatory follicles decreased before ovulation. Relevant epidemiological studies [15,16] also showed that smoking women of childbearing age were usually accompanied with a low rate of pregnancy or a high rate of abortion and/or infertility.…”
Section: Discussionmentioning
confidence: 99%
“…An experiment [13] on rats shows that prenatal expoused to BaP leads offsprings premature ovarian failure and ovarian tumorigenesis. A Study concerning the effect of PAH on follicular growth [14] showed that mice exposed to cigarette smoke could reduce antral follicles, therefore leading to appropriate preovulatory follicles decreased before ovulation. Relevant epidemiological studies [15,16] also showed that smoking women of childbearing age were usually accompanied with a low rate of pregnancy or a high rate of abortion and/or infertility.…”
Section: Discussionmentioning
confidence: 99%
“…High fat diet fed mice have increased levels of apoptosis in cumulus oocyte complexes and granulosa cells (Wu et al , 2010) and reduced cardiac Cx expression in female rats (Aubin et al , 2010), potentially supporting that obesity alters CX protein abundance. Additionally, DMBA altered Cx gene expression in neonatal ovaries (Ganesan and Keating, 2014), however, the effect of DMBA on Cx gene expression in adult mouse ovaries has not yet been studied. Thus, the impacts of both DMBA exposure and progressive obesity on ovarian Cx mRNA and protein abundance were investigated in ovaries from adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Protein was isolated from whole ovaries (n = 4–5) by homogenization in tissue lysis buffer containing protease and phosphatase inhibitors as previously described (Ganesan and Keating, 2014). Briefly, homogenized samples were placed on ice for 30 min, followed by two rounds of centrifugation at 10,000 rpm for 15 min and protein concentration was measured using a standard BCA protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations